Influence Net Profit Margin, Debt to Equity Ratio, Return on Assets and Current Ratio Against Effective Tax Rate: (In Sub Sector Companies Coal Mining Companies Listed on the Indonesia Stock Exchange 2016-2023) - Melanie, Melanie; Febriyanti, Diah (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
Tax is one of the main sources of funding for the Indonesian economy, where taxes are very important in supporting Economic and social development activities that require large funds. Therefore, the government tries to pick up taxes until it reaches the optimal point. Although various tax reform efforts have been made to increase state revenue, challenges still become problems that cause reception tax not yet reach the potential maximum. Research aims to analyze the influence of Net Profit Margin (NPM), Debt to Equity Ratio (DER), Return On Assets (ROA), and Current Ratio (CR) to Effective Tax Rate (ETR) on Sub- Sector Companies Coal Mining listed on the Indonesia Stock Exchange 2016-2024. Method research used is quantitative with an approach descriptive and verifiable with the type of data used, namely secondary data. Data collection techniques are obtained from the Annual Report on sub-sector companies in coal mining listed on the Indonesia stock exchange for the period 2016-2023 through the official Indonesia stock exchange and companies. Samples were taken using purposive sampling, namely election samples based on criteria appropriate to objective research. Based on criteria applied from 21 sub-sector companies in coal mining from 2016-2023, there are 7 Sub - sector companies mining that can made into the sample in research this is for measure the magnitude influence sample to be done a study using assumption test classic analysis multiple linear regression, analysis coefficient Person Correlation ( Product Moment ) and analysis coefficient determination ( R^2) and testing hypothesis in the form of Partial Test (t-test) and Simultaneous Test ( F test ). Data processing using the application Statistical Product and Service Solution version 30.0. Through the Partial Test (t-test), the results of the research show that the variable Current Ratio is influential and significant to the Effective Tax Rate. In addition, through coefficient test results determination ( R^2) shows the influence of the variables Net Profit Margin, Debt to Equity Ratio, Return on Asset, and Current Ratio to Effective Tax Rate by 28.09%.